Integration intrapreneurship: Implementing innovation in a public healthcare organization - Perrin Moss; Nicole Hartley; Trevor Russell (Journal of Innovation and Entrepreneurship, 2022)
As global events impact the way organizations operate and innovate in response to regional, workforce and consumer needs, the concept of intrapreneurism is attracting growing interest from policymakers and executives, particularly within the healthcare sector. The aim of this study was to capture the key learnings from the implementation of a telementoring pilot, to understand how intrapreneurship can embed innovation within an established organization to effect more integrated healthcare.
Keywords: 650; Australia; Healthcare; Integration; Intrapreneurship; Project ECHO; Telementoring